2019
DOI: 10.3748/wjg.v25.i10.1259
|View full text |Cite
|
Sign up to set email alerts
|

Endoloop ligation after endoscopic mucosal resection using a transparent cap: A novel method to treat small rectal carcinoid tumors

Abstract: BACKGROUNDLocal endoscopic resection is an effective method for the treatment of small rectal carcinoid tumors, but remnant tumor at the margin after resection remains to be an issue.AIMTo evaluate the efficacy and safety of resection of small rectal carcinoid tumors by endoloop ligation after cap-endoscopic mucosal resection (LC-EMR) using a transparent cap.METHODSThirty-four patients with rectal carcinoid tumors of less than 10 mm in diameter were treated by LC-EMR (n = 22) or endoscopic submucosal dissectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Though statistical significance was not reached, this could be the result of the low absolute number of recurrence due to limited follow‐up of 12‐48 months and the high natural survival rate of rectal carcinoid tumors. The use of EMR was associated with a 4‐fold increase in the risk of additional procedures, which is consistent with existing studies that attribute this to lymphovascular invasion and the failure to achieve complete resection margins 21,23,25,27,29,40,41 …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Though statistical significance was not reached, this could be the result of the low absolute number of recurrence due to limited follow‐up of 12‐48 months and the high natural survival rate of rectal carcinoid tumors. The use of EMR was associated with a 4‐fold increase in the risk of additional procedures, which is consistent with existing studies that attribute this to lymphovascular invasion and the failure to achieve complete resection margins 21,23,25,27,29,40,41 …”
Section: Discussionsupporting
confidence: 84%
“…The detailed PRISMA flowchart of this review is shown in Figure 1. In total, four articles originated from Japan, 21–24 10 originated from South Korea, 25–34 and eight were from China, 35–42 respectively; 21 of these studies were retrospective cohort studies, while the other was a prospective cohort study. This review summarizes the data from 655 ESD and 705 EMR procedures, and thus summarized results from the resection of 1360 rectal lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, advanced EMR techniques have been evaluated to improve local R0 rate. The most frequently used techniques are EMR-C and EMR-L, with R0 rates between 80 and 100% [4][5][6]17]. Another established resection technique for rectal NETs is ESD; however, this method is challenging, more complicated, and especially in western countries limited to few specialized centers.…”
Section: Discussionmentioning
confidence: 99%
“…Another established resection technique for rectal NETs is ESD; however, this method is challenging, more complicated, and especially in western countries limited to few specialized centers. Therefore, it is not surprising that R0 resection rate in recent Asian studies is about 90 to 100% while the only European study found only about 80% [4][5][6]. The main reason for incomplete resection of rectal NETs are remaining tumor cells in the deeper part of the submucosal layer; therefore, histopathological R1 situation sometimes occurs at the vertical margin of resected specimens, even if EMR-L/C or ESD technique is used [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation